The acceptability and cost of a home-based chlamydia retesting strategy: findings from the REACT randomised controlled trial. (December 2015) - Smith, K.; Kaldor, J.; Hocking, J.; Jamil, M.; McNulty, A.; Read, P.; Bradshaw, C.; Chen, M.; Fairley, C.; Wand, H.; Worthington, K.; Blake, S.; et al.
Abstract Background Chlamydia retesting three months after treatment is recommended to detect reinfections, but retesting rates are typically low. The REACT (retest afterChlamydia trachomatis ) randomised trial demonstrated that home-based retesting using postal home-collection kits and SMS reminders, resulted in substantial improvements in retesting rates in women, heterosexual men and men who have sex with men (MSM), with detection of more repeat positive tests compared with SMS reminder alone. In the context of this trial, the acceptability of the home-based strategy was evaluated and the costs of the two strategies were compared. Methods REACT participants (200 women, 200 heterosexual men, 200 MSM) were asked to complete an online survey that included home-testing acceptability and preferred methods of retesting. The demographics, sexual behaviour and acceptability of home collection were compared between those preferring home-testing versus clinic-based retesting or no preference, using a chi-square test. The costs to the health system of the clinic-based and home retesting strategies and the cost per infection for each were also compared. Results Overall 445/600 (74 %) participants completed the survey; 236/445 from the home-testing arm, and 141 of these (60 %) retested at home. The majority of home arm retesters were comfortable having the kit posted to their home (86 %); found it easy to follow the instructions and collect the specimens (96 %); were confident they had collected the specimens correctly (90 %); and reported no problems (70 %). Most (65 %) preferred home retesting, 21 % had no preference and 14 % preferred clinic retesting. Comparing those with a preference for home testing to those who didn't, there were significant differences in being comfortable having a kit sent to their home (p  = 0.045); not having been diagnosed with chlamydia previously (p  = 0.030); and living with friends (p  = 0.034). The overall cost for the home retest pathway was $154 (AUD), compared to $169 for the clinic-based retesting pathway and the cost per repeat infection detected was $1409 vs $3133. Conclusions Among individuals initially diagnosed with chlamydia in a sexual health clinic setting, home-based retesting was shown to be highly acceptable, preferred by most participants, and cost-efficient. However some clients preferred clinic-based testing, often due to confidentiality concerns in their home environment. Both options should be provided to maximise retesting rates. Trial registration The trial was registered with the Australia New Zealand Clinical Trials Registry on September 9, 2011:ACTRN12611000968976 .